SYSTEM IDENTIFICATION BASED PROXY MODELING OF A RESERVOIR UNDER SECONDARY RECOVERY - NEGASH, BERIHUN MAMO (2018)
Exploiting the full potential of physics based numerical reservoir models is challenging due to the 10s of hours required to perform a single simulation for many time steps. Currently, proxy models based on reduced order, response surface and surrogate reservoir modeling are used to replace the role of these numerical models and reduce the computational time.